(untitled) (Global Journal of Human-Social Science, 2013)
In a survey study of police officers in Alabama, this paper assesses how demographic factors of police officers, their reception of training on cultural diversity, and the awareness of their department’s written policy on bias-based policing are related to their perception of bias-based policing practices in their department. To achieve the goal of the present study, a survey of 400 officers was used to run multivariate logistic regression analyses. Three variables display significant association with a police officer’s perception regarding witnessing bias-based policing practices. Officers with younger age group, higher education, and longer work experience in the department are more likely to say that they have witnessed bias-based policing practices as compared with their counterparts with older age groups, lower education, and shorter work experience.